2022
DOI: 10.52201/cej19bujs9747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roost management on populations trends of Rhinolophus hipposideros and Rhinolophus ferrumequinum in Britain and Ireland

Abstract: After a significant population decline during the 20th century, populations of both greater and lesser horseshoe bats have increased over recent decades in Britain and populations of lesser horseshoe bats have increased in Ireland. Vincent Wildlife Trust (VWT) acquired 37 bat reserves since the 1980s with the aim to safeguard the sites and enhance the roosting and hibernation conditions in buildings that were often derelict and sub-optimal for bats. These measures have resulted in a strong population size incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to Leitl (2021), continuous population growth was observed in the years after installation due to increased survival and higher reproductive success. Since Berthinussen et al (2014) reported a general lack of international literature about the effects of hot boxes, only very few international (Wright et al 2022;Zingg et al 2022) and national (Leitl 2021; Dietz &Dietz 2021) studies became available in the meantime.…”
mentioning
confidence: 99%
“…According to Leitl (2021), continuous population growth was observed in the years after installation due to increased survival and higher reproductive success. Since Berthinussen et al (2014) reported a general lack of international literature about the effects of hot boxes, only very few international (Wright et al 2022;Zingg et al 2022) and national (Leitl 2021; Dietz &Dietz 2021) studies became available in the meantime.…”
mentioning
confidence: 99%